PM - Vidyalaxmi Scheme for Empowering Middle Class Youths to Pursue Quality Higher Education - Dr. H. M. Naveen (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
The PM Vidyalaxmi scheme, a significant initiative to provide financial support to meritorious students under the Central Sector. PM Vidyalaxmi is another concrete step towards implementation of NEP. The scheme will help universalise access to 21st-century higher education for India’s talented youth. He also mentioned that with an outlay of ₹3,600 crore, the scheme will remove obstacles to higher education and enable the yuva shakti of the country to pursue their dreams. Collateral-free and guarantor-free education loans under PM Vidyalaxmi will maximise access to higher education for meritorious students and ensure that financial constraints do not prevent students from pursuing education. The students having annual family income of up to ₹8 lakh shall be eligible to get 3% interest subvention on education loans up to ₹10 lakh and loans up to ₹7.5 lakhs shall be eligible for 75% credit guarantee. Education loans will be facilitated through a transparent, studentfriendly and digital application process that will be common to all banks. Education loans under PM Vidyalaxmi will be facilitated to students securing admissions in the top 860 HEIs of the country based on NIRF. This will cover more than 22 lakh students every year. The financial assistance to meritorious students is a key recommendation of NEP 2020 and PM Vidyalaxmi is another concrete step towards implementation of NEP. PM Vidyalaxmi will empower millions of students from the poor and middle class. The PM Vidyalaxmi scheme, is a new initiative under the Central Sector aimed at providing financial support to meritorious students, ensuring that financial constraints do not hinder access to higher education. This scheme is a significant step in realizing the vision outlined in the National Education Policy (NEP) 2020, which emphasises the need for financial assistance to be made available to deserving students through various mechanisms in both public and private higher education institutions (HEIs).